Embalagens flexíveis para alimentos: produção, tecnologia bag e regulamentação - Leite, Samara Leme de Almeida (Universidade Federal de São Carlos, 2025)
The packaging market in Brazil has shown steady growth, driven by factors such as increased consumption, technological innovations, and a focus on sustainability. In the food sector, the choice of specific packaging is crucial to preserving quality, protecting consumers' health, and meeting sustainability criteria. Among the available options, flexible plastic packaging, especially the Bag system, stands out for its high protection capacity, practicality, and efficiency in preserving food quality and safety. This study conducted a literature review on food packaging, focusing on flexible packaging and highlighting its efficiency as barriers against moisture and oxygen. Additionally, it emphasized the importance of bag technology, a solution that combines strength and efficiency in the storage and transportation of food. The study addressed the properties of the materials used, applicable regulations, and the relevance of flexible packaging in the current food industry landscape. However, compliance with food safety standards and challenges related to sustainability remain significant concerns. It is concluded that the continuous development of food packaging technologies, such as the bag system, is essential to meet market demands and environmental concerns, promoting practical and efficient solutions for the industry and consumers alike.
Flexible food packaging: production, bag technology and regulation
Keywords: Embalagens plásticas; Conservação de alimentos; Inovação em embalagens; Plastic Packaging; Food Preservation; Packaging Innovation; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS; 9. Indústria, Inovação e Infraestrutura